Better detoxifying effect of ripe forsythiae fructus over green forsythiae fructus and the potential mechanisms involving bile acids metabolism and gut microbiota - Wang, Tao; Li, Xu-Jiong; Qin, Ling-Hao; Liang, Xue; Xue, Huan-Huan; Guo, Jing; Li, Shi-Fei; Zhang, Li-Wei (Frontiers in Pharmacology, 2022)
Forsythiae Fructus (FF), the fruit of Forsythia suspensa (Thunb.) Vahl. (Lianqiao), is one of the most fundamental herbs in Traditional Chinese Medicines (TCM), mainly due to its heat-clearing and detoxifying effects. There are two types of FF, the greenish fruits that start to ripen (GF) and the yellow fruits that are fully ripe (RF), called “Qingqiao” and “Laoqiao” referred to the Chinese Pharmacopoeia, respectively. It undergoes a complex series of changes during the maturation of FF. However, the clinical uses and preparation of phytopharmaceuticals of FF have not been distinguished to date. Moreover, there is limited information on the study of the difference in pharmacological activity between RF and GF. In this study, a rat model of bile duct ligation (BDL)-induced cholestasis was used to compare the differences in their effects. RF was found to have better results than GF in addressing toxic bile acids (BAs) accumulation and related pathological conditions caused by BDL. The underlying mechanism may be related to the interventions of gut microbiota. The results of the present study suggest that the better detoxifying effect of RF than GF may be indirectly exerted through the regulation of gut microbiota and thus the improvement of BAs metabolism.